FREQUENCY OF DIABETIC RETINOPATHY IN HYPERTENSIVE DIABETIC PATIENTS IN A TERTIARY CARE HOSPITAL OF PESHAWAR, PAKISTAN - Rahman, Shafiqur; Nawaz, Rab; Khan, Ghulam Jillani; Aamir, Azizul Hasan (Journal of Ayub Medical College Abbottabad, 2011)
Background: Diabetic retinopathy is a common microvascular complication of both type 1 and type 2 diabetes mellitus. If left untreated, it can progress to serious visual disability. Coexistence of hypertension with diabetes has been described as another risk factor adding to the problem. We designed this study to assess the occurrence of diabetic retinopathy in hypertensive diabetic patients of this region and to compare it with normotensive diabetic patients. Methods: This cross-sectional study was carried out on 200 previously diagnosed diabetic patients. Apart from routine examination and investigations, retinopathy and blood pressure assessment of each patient was done using standard techniques. Hypertensive diabetic subjects (Group-I, n=107) were compared with non-hypertensive diabetics (Group-II, n=93) for the presence of retinopathy. Results: Retinopathy and hypertension were observed in 51% and 53.5% of the total diabetic patients respectively. Hypertensive diabetic patients had significantly higher percentage of retinopathy compared to non-hypertensive diabetic patients (58 vs 43%; p<0.05). Conclusion: Retinopathy and hypertension are highly prevalent in our diabetic patients. The proportion of retinopathy is significantly more in hypertensive as compared to normotensive diabetics. Keywords: Diabetes Mellitus, Diabetic Retinopathy, Hypertension, Prevalence, Tertiary care